2004
DOI: 10.1128/mcb.24.8.3168-3179.2004
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and Gamma Interferon Specifically Increase K15 Keratin Gene Transcription

Abstract: Basal layers of stratified epithelia express keratins K5, K14, and K15, which assemble into intermediate filament networks. Mutations in K5 or K14 genes cause epidermolysis bullosa simplex (EBS), a disorder with blistering in the basal layer due to cell fragility. Nonkeratinizing stratified epithelia, e.g., in the esophagus, produce more keratin K15 than epidermis, which alleviates the esophageal symptoms in patients with K14 mutations. Hypothesizing that increasing the cellular content of K15 could compensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 58 publications
1
42
0
1
Order By: Relevance
“…However, corrective intervention directed at the genetic code per se may not be practical as an effective means of treatment. One way to build up mechanical resiliency in trauma-sensitive epidermis (45) might be to exploit the partial functional redundancy known to exist among select keratins (101)(102)(103) and other IF proteins (104,105) and to devise means to stimulate their endogenous expression in the skin of affected patients.…”
Section: Figurementioning
confidence: 99%
“…However, corrective intervention directed at the genetic code per se may not be practical as an effective means of treatment. One way to build up mechanical resiliency in trauma-sensitive epidermis (45) might be to exploit the partial functional redundancy known to exist among select keratins (101)(102)(103) and other IF proteins (104,105) and to devise means to stimulate their endogenous expression in the skin of affected patients.…”
Section: Figurementioning
confidence: 99%
“…IFN-y also affects other keratins such as K16 in healthy keratinocytes as it was reported by Barker et al, 1993. In contrast to K14, K5 and K15 which are principally produced in basal layer, K17 is only expressed in the suprabasal layer (Radoja et al, 2004) and therefore the replacement of K14 by K17 in EBS is not possible. Radoja et al, (2004) have reported that K15 is induced at the transcriptional level by IFN-y.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to K14, K5 and K15 which are principally produced in basal layer, K17 is only expressed in the suprabasal layer (Radoja et al, 2004) and therefore the replacement of K14 by K17 in EBS is not possible. Radoja et al, (2004) have reported that K15 is induced at the transcriptional level by IFN-y. They suggested that the production of K15 could remedy to cytoskeleton defects in EBS harboring KRT14 mutations by forming heterodimers withK5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations